A case report of neuroendocrine tumor of extrahepatic biliary tract - Yusuf, Muhammad; Taqwa, Muhammad (Surgical Residency Program Syiah Kuala University, 2023)
Background: A rare form of tumor is a neuroendocrine tumor (NET). According to the 2015 National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines in Oncology, all endocrine tumors of the digestive system should be treated with neuroendocrine tumors of the gastrointestinal system. The incidence of NET is 2.5 cases per 100,000 people annually on average. Since NET has a variety of clinical symptoms, it can be divided into functionally active and inactive types. This study aimed to present a neuroendocrine tumor of the extrahepatic biliary tract. Case presentation: An 18-year-old female with a lump in the upper right abdomen with intermittent pain that had been felt in the last 8 months. There was evidence of previous weight loss and an easy appetite. Physical inspection revealed a mass with a fixed, smooth, flat edge and solid consistency. A vesica felea enlargement and a normal wall were discovered on the CT scan. Stone and sludge were not detected. The choleducus and cystic duct were normal-looking, and a 0.5 cm spherical stone was present. Bile fluid was found to move smoothly from the ductus cysticus to the distal and into the ampulla of Vater. Our patient was diagnosed early with an intra-abdominal tumor. An intraoperative cystic tumor measuring 9x7x8 cm and attached to the duodenum was discovered at the pancreatic cap. The pancreatic uncinate process underwent tumor excision. The patient was managed post-op in a stable condition, and the tumor's histology revealed a carcinoid tumor. Conclusion: NET is a rare type of tumor, but two third of it occurs in the gastrointestinal system. It is hard to detect because of its heterogeneous nature and various clinical presentation. Surgery is the first-line therapy in this disease, followed by chemotherapy, radiotherapy, and tumor debulking as palliative management.